VITAMIN D: MULTIPLE IMPACTS, NEW PERSPECTIVES - Laura Florescu; Laura Mihaela Trandafir; Dana Elena Mindru; Oana-Raluca Temneanu (Amaltea Medical Publishing House, 2018)
Vitamin D deficiency is a global public health problem in all age groups, mainly caused by insufficient exposure to sunlight, inadequate diets, inefficient absorption and use, higher requirements or higher losses. Knowing the implications of vitamin D for the body and sensitive growth and development periods, it is important to perform biological determinations, to make proper prophylaxis and to intervene promptly when changes occur. The age groups recommended for vitamin D administration are infants (whether they receive natural, formula or complementary feeding) and adolescents. Besides the well-known role of vitamin D in phosphocalcic metabolism, there is an increasing debate about the involvement of vitamin D in the pathogenesis of non-musculoskeletal diseases.